Relationship Between Oil Revenues and Gross Domestic Product of Oman: An Empirical Investigation - Aslam, Neelufer; Shastri, Swati (International Journal of Economics and Financial Issues, 2019)
Oil revenues are a significant contributor to Oman’s total revenues. This study empirically examines the long run and short run causal relationship between oil revenues, Real GDP and Real GDP from petroleum activities of Oman from 1985 to 2017. The Johansen Cointegration test and Vector Error Correction Model are used to investigate the cointegrating, long run, and short run relationship. Direction of short run causality is examined through the Wald coefficient restriction test, VEC Granger/Block Exogeneity Test and pairwise Granger causality test. Results show that a statistically significant long run relationship exists between oil revenues, GDP and GDP from petroleum activities. In the short run, however, a weak significant relation exists between GDP and real oil revenues. Variance Decomposition of Forecast error of GDP shows that 48% of variation in GDP can be explained by oil revenues. Through Impulse Responses Function results, it is concluded that initially there is a sharp rise in oil revenues after which oil revenues tend to fall. Keywords: Real Oil Revenues, Real GDP, VECM JEL Classifications: E60, O11 DOI: https://doi.org/10.32479/ijefi.8805